Cooling Structure Design of High-Speed Permanent Magnet Synchronous Machine With Axial Ventilation Self-Cooling Rotor - Hao Luo; Yue Zhang; Huijun Wang; Guangwei Liu; Fengge Zhang (IEEE Access, 2024)
In order to address the challenges of high loss density, difficult heat dissipation, and irreversible demagnetization in high temperature of high-speed permanent magnet machine, an innovative cooling structure with axial ventilation and self-cooling rotor is proposed to enhance temperature distribution. The cooling efficiency of the cooling structure is defined, and the influence of the rotor vent on the electromagnetic and air friction loss is analyzed. The governing equation for the fluid flow in a rotating pipe is derived from a fluid model analysis of a ventilation hole rotating at any angle to the axis of rotation. The calculated results are validated against the results obtained from computational fluid dynamics. The sensitivity of rotor cooling performance to various control factors using the variance index method. Subsequently, the cooling structure was enhanced based on the findings of the analysis. The calculation results indicate that the heat dissipation effect of the axial ventilation self-cooled rotor has decreased by 4.17 °C compared to before the improvement. The temperature rise experiment verified the accuracy of temperature calculation and the effectiveness of the cooling structure, providing strong support for the design of axial self-ventilation cooling system for high-speed machines.